Is the level of serum lactate dehydrogenase a potential biomarker for glucose monitoring with type 2 diabetes mellitus? - Hsieh, Yu-Shan; Yeh, Min-Chun; Lin, Yan-Yu; Weng, Shuen-Fu; Hsu, Chung-Huei; Huang, Chen-Ling; Lin, Yu-Pei; Han, A-Young (Frontiers in Endocrinology, 2022)
Introduction Type 2 diabetes mellitus (T2DM) is a metabolic disorder due to defects in insulin secretion or insulin resistance leading to the dysfunction and damage of various organs. To improve the clinical evaluation of short-term blood glycemic variability monitoring, it is critical to identify another blood cell status and nutritional status biomarker that is less susceptible to interference. This study identifies the significance of serum lactate dehydrogenase (LDH) level among T2DM patients treated in outpatient clinics and investigates the relationship of LDH level with other variables. Methods This study comprised 72 outpatients with T2DM over 20 years of age. Blood samples were collected followed by a hematological analysis of serum glycated albumin (GA), LDH, fasting blood glucose, glycosylated hemoglobin, C-peptide, and insulin antibodies (insulin Ab). Results Serum LDH level was significantly correlated with GA (p < 0.001), C-peptide (p = 0.04), insulin Ab (p = 0.03), and thyroid-stimulating hormone (TSH) levels (p = 0.04). Hence, we performed a linear regression analysis of hematological markers. GA (p < 0.001, r2 = 0.45) and insulin Ab (p < 0.001, r2 = 0.40) were significantly associated with LDH level. Then, we classified patients into low (<200 U/L) and high (≥200 U/L) serum LDH level groups, respectively. GA (p < 0.001), C-peptide (p = 0.001), and TSH (p = 0.03) showed significant differences in patients with high LDH levels compared with those in patients with low LDH levels. Conclusion In conclusion, we suggested that LDH level was independent of long-term but associated with short-term blood glucose monitoring. The results indicated that changes in serum GA induced cell damage and the abnormal elevation of the serum level of LDH may occur simultaneously with glycemic variability. It has been reported that many biomarkers are being used to observe glucose variability in T2DM. However, LDH could provide a more convenient and faster evaluation of glycemic variability in T2DM.